IMPROVING THE SERVICE EXCELLENCE OF SCHOOL ADMINISTRATIVE PERSONNEL THROUGH PRINCIPAL LEADERSHIP IN SMK NEGERI PADANG - Nellitawati Nellitawati; Singgih Ginanjar (Adisam Publisher, 2026)
The purpose of this study is to see how principals of public vocational schools in Padang City can lead their workforce to provide better and more efficient services. The existing phenomenon in the education industry is the low standard of service quality provided by administrative staff. The purpose of the predictors that influence principals' leadership is to improve the performance of school administrative staff. The purpose of this study is to find out how the administrative staff of public vocational high schools in Padang City can provide better and improved services under the direction of the school principal. To achieve the research objectives, this study employed a qualitative approach, conducted in accordance with the established criteria. 67 members of the school administration who became informants in the data collection process, which involved observations and interviews. The model approach developed by Miles and Huberman was used to scrutinise the qualitative data. The results showed that the quality of principals' leadership remains at a moderate level, as do their efforts to improve the standard of administrative services provided to SMK Negeri in Padang City. The research also shows that principals' leadership is a key factor in improving the quality of services provided by school administrative staff. To improve the standard of services provided by school administrative staff, it is recommended that principals engage more actively and creatively with education stakeholders and other administrative team members. Based on the findings, it can be concluded that to improve the quality of services provided by the school's administrative Staff and principals' leadership, it needs to be strengthened.